The Thought Comparisons Of Two Indonesian Islamic Reformers About Islamic Education; Ahmad Dahlan And Hasyim Asy’ari - Siska Ofanni Islamia (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
Ahmad Dahlan and Hasyim Asy'ari were reformers of Islamic education in the archipelago who were also founders of pre-independence Islamic organizations. Ahmad Dahlan was the pioneer of the founding of the Muhammadiyah Islamic organization, while Hasyim Asy'ari was the founder of the Nahdlatul Ulama Islamic organization. The purpose of education, according to Ahmad Dahlan, is an effort aimed at giving birth to a generation with high intellectual quality and having high religious knowledge, and ready to always prioritize the welfare of the community. Whereas Hasyim Asy'ari had the view that the most important thing in education is character building. Ethics is the face of education that can determine the dignity and self-esteem of humans. The research used by me belongs to the type of literature study because it relies on literacy sources. I used a qualitative approach and also used a descriptive analysis method when compiling the results of this study.